Skills in the Language Component of 10th Grade Students as a Basis for the Development of a Worktext - Cargason, iysa Mae; Bangkulit, Nor-en (International Journal of Arts, Sciences and Education, 2025)
This study aims to measure the level of skills of Grade 10 learners as basis for the development of a worktext. This aims to emphasize the enhancement of students’ skills and knowledge in an effective and enjoyable manner. The study was conducted at San Miguel National High School, Barangay San Miguel, Norala, South Cotabato, during the third quarter of school year 2024-2025. Using stratified random sampling, a total of fifty students were selected as respondents for the study. The research utilized the Research and Development (R&D) design, which involves a thorough study and development of a teaching and learning tool. Based on the results, it was found that the students’ skill level was advanced. The students possess sufficient knowledge in using words to form statements. In the validation of the developed worktext, the results of the expert validation indicated that the material is highly valid, stating that the resource has sufficient content as a teaching tool. The output of this study was accepted by both teachers and students, with the description being highly acceptable. The study revealed that there was no significant difference in the acceptance results between the teachers and students. Therefore, the outcome of this study will serve as a foundation and instrument to continue the development of tools that will aid in the teaching and learning process.